Consecutive Tandem Cycloaddition between Nitriles and Azides; Synthesis of 5-Amino-1H-[1,2,3]-triazoles - Gomes, Ana T. P. C.; Martins, Priscila R. C.; Rocha, David R.; Neves, Maria G. P. M. S.; Ferreira, Vitor F.; Silva, Artur M. S.; Cavaleiro, José A. S.; da Silva, Fernando de C. (Synlett, 2013)
Novel 5-amino-1H-1,2,3-triazoles were synthesized by a new synthetic route that involves consecutive tandem cycloaddition between nitriles and azides.
Keywords: triazoles; tandem cycloaddition; consecutive reaction; nitriles; azides